Escape theory and materialism: an experimental paradigm for self-blame - Radetzki, Phillip A. (My University, 2017)
Escape theory proposes a six-step process in which materialists’ forthcoming self-awareness reveals a general dissatisfaction with life, thereby stimulating a pursuit toward the attainment of tangible objects as a form of compensation. Although there is sufficient evidence supporting the overall plausibility of escape theory, Donnelly and colleagues acknowledge that further research regarding specific steps would enhance its strength. Moreover, a significant portion of findings on materialism are correlational, thereby making research utilizing experimental paradigms of particular value. The present study will investigate escape theory’s second step, self-blame, with an experimental design. The participant pool (n=300) will consist of undergraduate students with materialistic orientations. As a cover story, participants will be presented two unrelated studies regarding perceptions of interpersonal conflict and the impact of website design on the psychology of the online shopper. In the first portion, participants will be randomly assigned to a neutral condition or a condition designed to induce self-blame. Both conditions involve exposure to a vignette with a filler questionnaire. In the second portion, participants will explore a fictitious online store and purchase desired items. There will be 30 categories of product. Each category will contain three versions of the product corresponding to different levels of materialistic value. Within a materialistic population, those primed to experience self-blame are predicted to demonstrate significant bias toward products high in materialistic value. If the hypothesis is supported, the proposed study will add experimental evidence for the causal role of self-blame in the maladaptive attitude toward wealth and material objects.
Presented on April 24, 2017 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: escape theory; self-blame